Recent Trends in Microencapsulation for Smart and Active Innovative Textile Products - Valdes, Arantzazu; Ramos, Marina; Beltran, Ana; Garrigos, Maria C. (Current Organic Chemistry, 2018)
The industrial interest for microencapsulation techniques to produce innovative materials has increased in the last years. Microencapsulation shows several advantages for textile industries since active compounds, such as vitamins, essential oils, antimicrobials and/or antibiotics can be isolated to protect them from environment factors (oxygen, light, moisture and temperature). Microcapsules are also used for the controlled release of fragrances or even heat, to mask undesired properties of the active components and to convert liquid substances into solids with increased compatibility. In this review, the application of microencapsulation techniques to obtain innovative materials for the textile sector has been highlighted. The main known techniques have been briefly described, including interfacial, suspension and in situ polymerizations as well as spray drying, complex coacervation, centrifugal extrusion processes, fluidized-bed-coating and sol-gel techniques. Different mechanisms have been also described based on the different properties offered by permeable or non-permeable capsules. Finally, the development and application of microencapsulation in smart (phase change materials, photochromic, thermochromic and flame retardant microcapsules) and active textiles, including antimicrobials and the use of different additives with pharmaceutical and/or medical properties, insect-repellent systems and fragrant solid carrier materials have been briefly discussed.
Keywords: Microencapsulation